Investigations on electrical characteristics of (PbO)30(CuO)x(As2O3)(70-x) glass ceramics. Issue 8 (1st June 2017) - Kumar, K. Naresh; Suresh, B.; Ingram, A.; Kostrzewa, M.; Bragiel, P.; Kumar, V. Ravi; Veeraiah, N.
Abstract: This study is mainly focused on dielectric properties of lead arsenate glasses crystallized with different concentrations of CuO over continuous ranges of frequency (3 Hz −100 kHz) and temperature (300–633 K). The glasses were prepared by melt quenching technique and were heat treated for prolonged time for ceramization. Prepared samples were characterized by XRD, SEM and DSC techniques. SEM studies indicated that the samples are composed of small crystal grains of the size varying from 0.2 to 1.0 µm cemented with the residual glass phase. XRD studies indicated CuAs2 O4, Pb2 Cu7 (AsO4 )6 and Cu2 O are the main crystal phases developed during the crystallization. Optical absorption studies confirmed the presence of copper ions in Cu + valence state in addition to Cu 2+ state and the fraction of Cu + ions is found to increase with the content of CuO. The optical band gap exhibited increasing trend with CuO content. IR spectral studies indicated an increase of degree of polymerization of the glass network with the CuO content. The observed variations of dielectric parameters with frequency, temperature and CuO content are discussed using different polarization mechanisms. The dielectric relaxation effects exhibited by the loss tangent and the electric moduli are analyzed using graphical method and observed relaxation effects are attributed to the complexes of divalent copper ions with oxygens. The impedance diagrams indicated increase of bulk resistance of the samples with increase of CuO content. The ac conductivity exhibited a decreasing trend with increase of CuO content. The conduction phenomenon is explained using polaron hopping between Cu + and Cu 2+ ions. The temperature independent part of the conductivity is explained using quantum mechanical tunneling (QMT) model. Finally, it is concluded that the insulating strength of the material increased with CuO content and such materials may be useful as electrical insulators in the low temperature region